The Effect of Coleus Amboinicus Lour (Jintan Leaf) Steam Bolu on the Quantity of Breast Milk in Postpartum Mothers in the Working Area Samboja Health Center - Desya Regita Biantari; Dwi Hendriani; Dewi Rinda Astuti (PT FORMOSA CENDEKIA GLOBAL, 2023)
It is known that the Samboja Community Health Center has exclusive breastfeeding coverage in 2020 of (62.44%), in 2021 it has decreased to (46.24%), even though the exclusive breastfeeding coverage target at the Samboja Community Health Center is 50%. Low breast milk coverage is due to the mother's failure in the breastfeeding process due to the quantity of breast milk. Increasing the quantity of breast milk can be done by providing lactogenic foods with lactogagum effect such as Coleus Amboinicus Lour (cumin leaves). The aim is to find out the effect of steamed Coleus Amboinicus Lour (Cumin Leaves) sponge cake on the quantity of breast milk in postpartum mothers. This type of research is quasi-experimental, with a design using a pre and post test non-aquavalent control group. The quantity of breast milk before giving steamed Coleus Amboinicus Lour (Cumin Leaves) sponge cake to postpartum mothers in the intervention group and control group was 6.50. There is an effect of steamed Coleus Amboinicus Lour (Cumin Leaves) sponge cake on the quantity of breast milk in postpartum mothers.